The Association between Abnormal Vaginal Flora and Cytological Evidence of HPV with Prematurity in High-Risk Pregnant Women - Alana Dantas Freire; Ada Isa Custódio; José Queiroz Filho; Janaína Crispim Freitas; Ana Katherine Gonçalves; Ricardo Ney Cobucci (Gynecology Obstetrics & Reproductive Medicine)
Objective: To evaluate the association between abnormal vaginal flora and cytological evidence of HPV with prematurity in high-risk pregnant women.